Compounding crises of social reproduction: Microfinance, over-indebtedness and the COVID-19 pandemic. (December 2020) - Brickell, Katherine; Picchioni, Fiorella; Natarajan, Nithya; Guermond, Vincent; Parsons, Laurie; Zanello, Giacomo; Bateman, Milford
Highlights: Reliance on microfinance for everyday survival will be deepened by the COVID-19 pandemic. The majority of microfinance borrowers globally are women. Servicing microfinance loans will heighten burdens of (un)-paid work that women undertake as part of social reproduction. Over-indebtedness leads to women's bodily and emotional 'depletion'. The global public health crisis of COVID-19 represents a major challenge to gender equality and sustainable development. Abstract: The COVID-19 pandemic has hit at a time when microfinance is at its historical peak, with an estimated 139 million microfinance customers globally. Cambodia's microfinance sector is one of the fastest growing, and like others in the Global South has moved from offering entrepreneurial capital to everyday liquidity, and even disaster relief. In this Viewpoint, however, we argue that the promotion of microfinance as market-based relief and recovery from the pandemic should be a source of concern, not comfort. We firstly suggest that as a result of the health and economic impacts associated with COVID-19, credit-taking is likely to escalate further in terms of the number of borrowers and loan amounts. Second, we contend that a growing reliance on MFIs will leave households undernourished, and further vulnerable to its disciplining and extractive impulses. Third, we argue that the interplay between over-indebtedness, pre-existing malnutrition challenges, and the global public health crisis of COVID-19 represents a major challenge to gender equality and sustainable development. Coordination between the Cambodian government, microfinance lenders, international investors, and development partners is vital to offer debt relief. Furthermore, to reverse the reliance of so many households on the microfinance industry for survival, inclusive socio-economic policies and public welfare services must be prioritised.